Management's Impact on Micro, Small, and Medium Enterprise (MSME) Development in Tourism: Driving Local Economic Growth in Lebak District - Eka Prasetiawan; Dudi Permana; Yuli Harwani; Yanto Ramli (Management Analysis Journal, 2024)
This study aims to investigate the role of management in the development of Micro, Small, and Medium Enterprises (MSMEs) in the tourist sector as a catalyst for local economic development in the Lebak District. The study` takes a qualitative methodology, with government agencies and MSME actors in Lebak District serving as research informants. The findings emphasize the importance of effective management techniques in the development and growth of MSMEs operating in tourist attraction regions. Strong government support through local rules, streamlined licensing procedures, and the availability of suitable business locations are all important elements impacting MSME development. However, problems such as limited availability to raw materials, marketing limits, and financial constraints. It is crucial to focus on improving management competencies for the MSME actor  in order to handle these difficulties and boost MSME development. This includes assisting with infrastructure development, developing human resource skills, and encouraging collaboration among government agencies, local communities, and MSME actors. Furthermore, the government should make the finance more accessible and provide business training programs to empower MSMEs in the tourism sector and drive local economic growth in the Lebak District. Effective management practices are critical for guaranteeing MSMEs' long-term viability and competitiveness in the fast-paced tourist business.